Pendekatan Ilmu Humaniora terhadap Transformasi Nilai Sosial dalam Masyarakat Berbasis Teknologi Digital - Supriono, Ajeng Ayu; Haridah, Fatma; Supratman, Supratman (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The transformation of social values in technology-based digital societies is a multidimensional phenomenon that reshapes ways of thinking, patterns of interaction, and the construction of social meaning. Digital technologies not only enhance efficiency and accelerate communication, but also reconfigure moral orientations, social relations, and cultural structures. This study aims to analyze the transformation of social values through a humanities-based approach that positions humans as the central subjects within technological change. The research adopts a qualitative method using a socio-philosophical and critical humanities perspective. Data are collected through a systematic literature review of scholarly works addressing digital humanism, value transformation, and the relationship between technology and society. The analysis applies thematic and interpretative techniques to identify patterns of social value change and examine their implications for contemporary social life. The findings indicate that digital technology functions as a new cultural space that promotes values such as instrumental rationality, efficiency, and individualization, while simultaneously challenging solidarity, empathy, and social responsibility. A humanities approach provides a critical and ethical framework to interpret these shifts beyond purely technical explanations. Digital humanism emerges as a key normative concept that offers guidance to ensure that social value transformation remains aligned with human dignity and moral responsibility. This study affirms that integrating the humanities into the analysis of digital society is essential for ensuring that technological development supports sustainable, equitable, and human-centered social values.